A literature review of biomarkers used for diagnosis of relative energy deficiency in sport - Dvořáková, Kristýna; Paludo, Ana Carolina; Wagner, Adam; Puda, Dominik; Gimunová, Marta; Kumstát, Michal (Frontiers in sports and active living, 2024)
INTRODUCTION: The review aims to summarize the markers used in diagnosing relative energy deficiency in sport (REDs) and compare them with the REDs CAT2 score. METHODS: A systematic search was performed in the PubMed, Web of Science, and SPORTDiscus databases during April 2023. The descriptors used were "athlete" AND "REDs," along with respective entry terms. The selection process followed the PRISMA 2020 recommendations, identifying 593 records, from which 13 studies were ultimately selected. Seventy-nine markers were identified and categorized into six groups: bone mineral density (BMD), metabolic resting rate, blood biomarkers, anthropometrics, nutritional intake, and performance parameters. The most frequently utilized biomarkers included BMD, anthropometric parameters (e.g., body mass index, body mass, and fat mass), and the triiodothyronine (T3) concentration. RESULTS: According to the REDs CAT2 pointed indicators, the biomarkers varied among the studies, while 7 out of the 13 included studies achieved a ≥60% agreement rate with this tool. The prevalence of low energy availability, an etiological factor in the development of REDs, was detected in 4 out of 13 studies, with an average of 39.5%. CONCLUSION: In conclusion, this review highlights the most commonly used markers in diagnosing REDs, such as BMD, anthropometric parameters, and T3 hormone concentration. Due to the current inconsistencies, standardizing diagnostic methodologies is crucial for future research. By focusing on widely used markers, this review aids future research planning and result interpretation and points out the ongoing need for methodological consistency in evolving diagnostic tools. SYSTEMATIC REVIEW REGISTRATION: https://www.crd.york.ac.uk/, PROSPERO (CRD42022320007).